A Flavone Glycoside, Robinitin-7-O-β-D-Glucopyranoside from Alternanthera sessilis - Sahu, B.R.; Chakrabarty , Ajita (Asian Journal of Chemistry, 2010)
The present paper deals with the isolation and structural elucidation of a flavone glycoside robinitin-7-O-β-D-glucopyranoside.